Healthcare professionals' perceptions of impacts of the Covid-19-pandemic on outpatient care in rural areas: a qualitative study - Madlen Hoerold; Marc Gottschalk; Carla Maria Debbeler; Heike Heytens; Saskia Ehrentreich; Ruediger C. Braun-Dullaeus; Christian Apfelbacher (BMC, 2021)
Abstract Background Measures to manage the COVID-19 pandemic have led to impacts on healthcare systems and providers worldwide. Outpatient healthcare professionals (HCPs) provide the majority of patient care. Insight into their experiences during a pandemic is rare. Therefore, we explored how primary and secondary care HCPs in a rural area in Germany experienced their work during the pandemic and what health-related outcomes they perceived in their patients. In this context, we also examined the impact on access to and utilization of healthcare and working conditions. Methods We conducted a qualitative interview study with outpatient HCPs. We recruited by e-mail, telephone, professional networks and personal contacts. Data were collected between August 2020 and January 2021. All interviews were audio recorded, transcribed, and analysed using qualitative content analysis. Results Our sample consisted of 28 HCPs (15 family physicians, 7 cardiologists, and 6 non-physician assistants, 12 female) from Saxony-Anhalt, Germany. HCPs experienced fewer consultations as well as cancellations by hospitals and secondary care physicians, especially at the beginning of the Covid-19-pandemic, while they continued throughout to provide outpatient care. They quickly adopted changes in practice organisation and healthcare provision. There was a shift towards telephone consultations, home visits as well as unconventional consultations e.g. through the practice window. Family physicians used personal relationships to support utilization of healthcare and to avoid health-related effects. Social tension and burden seemed to interact with a perceived lack of preparedness, the pandemic-related changes in their working condition as well as access to and utilization of healthcare. Chronic disease monitoring was postponed, which could have consequences in the course of disease of patients. HCPs experienced effects on patients' psychological well-being. Conclusion Our study demonstrates the impacts of Covid-19-pandemic on outpatient care in rural areas and emphasizes its importance. HCPs experienced impacts on access to and utilization of healthcare, working conditions and health-related outcomes. Health policy should create a framework for healthcare to support outpatient care in rural areas with a looming undersupply of primary and secondary care in order to maintain healthcare and reduce pandemic impacts.